Influence of Cryopreservation on Phenotype and Functional Properties of Multipotent Mesenchymal Stromal Cells Derived From Different Sources - Volkova, Natalia; Vvedensky, Dmytro; Yukhta, Mariia; Goltsev Аnatoliy (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(3): 268–272